Ectopia cordis: a case report - Agrawal, Sujan Narayan; Joshi, Vivek K.; Sanapale, Sarita; Tiwari, Praveen C. (International Surgery Journal, 2018)
The Ectopia cordis is a rare congenital condition. It is characterized by the abnormal position of the heart outside the thoracic cavity, associated with defects in the parietal pericardium, diaphragm, sternum, and, in most cases, cardiac malformations. The reported prevalence is 5.5 to 7.9 per million live births. The designation Ectopia cordis was first proposed by Abott in 1998, although cases of patients with similar defects had been reported in past. Only 267 cases have been reported as of 2001, most (95%) associated with other cardiac abnormalities. A 10 hour old, normal, vaginally delivered, full-term male neonate, weighing 2020 grams was brought with an externally visible, beating heart over the lower chest wall. The antenatal period was uneventful, though no ultrasonography was done. The beating heart was covered with a membrane with greenish purulent matter over it, most probably, due to pseudomonas/proteus infection. Rest of the anterior abdominal wall was intact. Ectopia cordis is produced by segmental defects in mesodermal development in the third week of intrauterine life, and/or amniotic band syndrome that causes simultaneous cerebral and Thoraco-abdominal malformations. The existence of Ectopia cordis with severe congenital heart disease may be confirmed in the prenatal period by vaginal echocardiography at 10-12 weeks of gestation or by abdominal echocardiography by 20-22 weeks. Surgery is the only hope of survival, for such patients, although the overall success rate is very poor. In recent years, surgery has been attempted in one or two phases with variable results that depend, mainly on the type of associated heart disease.